Endovideo-assisted emergency surgeries in system of multiple-stage treatment of victims with severe craniofacial trauma - Yu. A. Shcherbuk; D. Yu. Madai; K. P. Golovko; O. D. Madai; A. Yu. Shcherbuk; S. V. Gavrilin; P. S. Sidorov; E. A. Gorshkov; A. O. Bumai; K. A. Absava (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The article presents the complex management of treatment in multiple trauma using endovideoassisted surgeries. MATERIAL AND METHODS. The authors demonstrated minimally invasive methods of treatment for victims with multiple trauma on the second stage of programmed multiple-stage surgery in order to eliminate life-threatening consequences and fix fractures of facial skeleton. These operations were performed during 12 hours after trauma. RESULTS. Programmed multiple stage treatment included the prevention or stop of asphyxia, bleeding and temporary fixation of fractures using extrafocal osteosynthesis and elements of primary plasty of soft tissues. Surgeons created conditions for intensive therapy (tracheostomy) using minimally invasive methods. CONCLUSIONS. Endovideo-assisted technique decreased trauma of surgical approach and allowed doctors to perform revision of complex anatomical structures, which were difficult to access. It expanded the volume and possibilities of surgical manipulations. Surgeons differentially removed foreign bodies and areas of necrosis. The method increased an accuracy of reconstructive surgeries and facilitated to monitoring of damaged structures.